Fondamentaux et variations pour l’observation des pratiques montessoriennes des écoles maternelles publiques françaises - Chrystel Huard (Recherches en Éducation, 2025)
This article shows the gradual development of a methodology designed to document "different" pedagogical prac-tices implemented by public school teachers in their classrooms. It is part of our doctoral research, which aims to publicize and understand the new practices inspired by Montessori pedagogy that have emerged since 2010. Thanks to a questionnaire survey carried out in 2016, we had shown that the practices declared by these teachers were highly heterogeneous, a fact that other research had also documented. We then drew up an initial typology of these practices according to the degree of closeness to Maria Montessori's original pedagogy. This time, the aim of our current research is to observe teaching practices, followed by self-confrontation interviews with the teachers of these classes. Pursuing the objective of reporting on the variety of these practices, we have drawn up a reference list of the fundamental principles of Montessori pedagogy, then constructed a new grid to identify observable criteria and elaborate a new classification of practices. We present this tool and the three stages in its construction, as well as its initial results.